Car engine breather icing - Horoufi, Aryan (Cranfield University, 2012)
Icing in an engine breather system can block the engine breather pipe, cause excessive crankcase pressure and degrade the engine performance. In this project, a numerical study, experimental tests and CFD analysis are employed in order to understand condensation and the extent of freezing inside a vertical pipe, a horizontal pipe and a T-joint pipe which are exposed to an external convective cooling. The pipe internal flow is assumed to be a vapour/air mixture. This study has led an evaluation of freezing in an engine breather pipe. The finding in this project highlighted the effects of the pipe internal flow condition (vapour mass fraction, relative humidity, mixture gas flow rate, and inlet relative humidity), the pipe external cooling condition (temperature and air velocity) and pipe thermal conductivity on condensation and extents of ice formation in the pipe. In the experimental study, a test rig has been designed and the condensation and freezing in the pipe have been tested at the Cranfield Icing Tunnel. The local pipe temperatures are measured to validate the numerical and the CFD analysis. The numerical study has led to develop a one dimensional code which used heat and mass analogy to model condensation and freezing in a vertical pipe exposed to a cold air flow (-20C). This code satisfactory predicts the trend and magnitude of the local temperatures and heat transfer coefficient along the vertical pipe at available test condition within an acceptable uncertainty of 25%. This study proposes an empirical correlation based on a degradation factor to evaluate heat transfer coefficient inside a vertical pipe. Its results fit with the experimental data within 15% uncertainty. The CFD methodology developed in this study is capable of predicting condensation rates, local temperatures, heat transfer coefficients and extent of freezing in the pipes with good agreement with the experimental results. The CFD model over predicts the breather pipe ice blockage time due to disparities between an actual engine operating condition and the CFD model. Therefore, an adjustment factor of 1.7 is proposed in this study to correlate the predicted blockage time. The results of this study can help Jaguar to establish guideline for future design of engines breather pipes.